Inequality and informality in transition and emerging countries - Roberto Dell'Anno (IZA World of Labor, 2016)
Higher inequality reduces capital accumulation and increases the informal economy, which creates additional employment opportunities for low-skilled and deprived people. Despite this positive feedback, informality raises problems for public finances and biases official statistics, reducing the effectiveness of redistributive policies. Policymakers should consider the links between inequality and informality because badly designed informality-reducing policies may increase inequality. However, convincing empirical evidence is still lacking and is usually limited to correlations rather than causal effects.
Keywords: D64; H41; J31; 330; informality; inequality; shadow economy